KELANTING INNOVATION (GRAND MOTHER CLASS OF CARE STUNTING ) EDUCATION AND LOCAL FOOD DIVERSIFIED IN PREVENTING STUNTING SIDOBANDUNG, BALEN, BOJONEGORO REGENCY - AZIZAH, NUR; Muslima Isnanda Putri, Evita; Muhidayati, Wiwik; lestari, puji (Universitas Airlangga, 2024)
Nutrition problems are still a concern for the Indonesian government to be resolved immediately, one of which is the problem of stunting. , Bojonegoro Regency's stunting prevalence rate is 23.9 percent, making Bojonegoro the district with the 13th highest stunting prevalence of 38 districts and cities in East Java. The prevalence of stunting which is still quite high can affect Indonesia's development performance because stunting has an impact on children's health status so that children become vulnerable to illness and has an impact on children's intelligence and quality of life, so handling it is still a government priority. The innovation of the KELANTING program (Stunting Caring Grandmother Class) is present by involving academics who act as references for solving problems based on research results (based on research) in the field of midwifery and nursing. So that it is able to increase the understanding of the community, especially grandmother caregivers, so that they are able to carry out care appropriately and get used to it. children to consume foods with balanced contents. The Klanting Program is carried out with Local Food Education and Diversification in Sidobandung Village, Balen District, Bojonegoro Regency